Estudo dos fatores que motivam, beneficiam e dificultam a implantação dos sistemas ISO 9001 e 14001 em empresas de engenharia de projetos e consultiva: modelagem usando os métodos dos mínimos quadrados e de superfícies de resposta - Franco, Marco Antonio Cortellazzi (2019)
Over the last decade, the number of companies providing engineering services that implemented quality management systems and environmental management systems, motivated among other factors, with the improvement of its image in the market, cost reduction, better competitiveness and pressure of customers, is increasing. Using theoretical models, in the last two decades several studies have been published seeking to identify the factors that induce organizations to implement standardized management systems, the benefits obtained from their implementation and the difficulties encountered. With the objective of contributing to these studies, this thesis seeks to identify the reasons, benefits and difficulties and integrate them into a mathematical model that indicates the influence of each one on the decision of Brazilian companies of Project Engineering and Consultancies to deploy the ISO 9001 quality management system and the ISO 14001 environmental management system. For this purpose, design of experiments, the least squares method and the response surface method was used. This research adopted a quantitative approach, with a survey with the fifty-nine largest Brazilian companies of project engineering and consultancy, the research instrument used was a questionnaire made available on the Internet for a period of approximately four months. From the fifty-nine companies contacted have been received sixteen complete questionnaires. The results obtained for ISO 9001 show that linear and quadratic models was adjusted to the system, the factor that most influenced in its implementation was the operational, the benefits obtained was related to the operational and financial factors and the difficulties, to the management of the company. For ISO 14001, the linear model was the most adjusted, the factor that had the greatest influence in its implementation was marketing, the benefits obtained was related mainly to the operational factor and the difficulties observed to the factor management of the company.